The Content of Photosynthetic Pigments in the Leaves of Galega officinalis L. and Galega orientalis Lam. Cultivars - Shymanska, Oksana; Vergun, Olena; Rakhmetov, Jamal; Fishchenko, Valentyna (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
The present study aims to investigate the differences in leaf pigment content of plants of cultivars of Galega L. species. Plant raw material was collected in the spring vegetation stage, budding stage, flowering stage, and fruitage. Biochemical analyze of determination of pigments content was carried out with fresh mass of leaves (100 mg) of cultivars of Galega officinalis L. and Galega orientalis Lam. It was conducted the extraction of pigments in acetone. Obtained acetone extracts of leaves were prepared according to Musienko et al. (2001) and measured at wavelengths 662 nm (chlorophyll a), 644 nm (chlorophyll b) and 440 nm (carotenoids). To calculate concentration (mg% of fresh mass) of pigments was applied the equation of Holm-Wettstein. It was found the maximal sign of chlorophyll a in the acetone extracts of Galega orientalis cv. NBS-75 (2.38 mg%) at the flowering stage and minimal – in the leaves of Galega officinalis cv. Harant (1.20 mg%) at the fruitage. Highest level of chlorophyll b concentration was identified for Galega orientalis cv. NBS-75 (0.58 m%) at the flowering stage and lowest – for Galega orientalis cv. Kavkazskiy branets (0.19 mg%) at the spring vegetation period. As result, maximal accumulation of carotenoid concentration observed in the leaves of the plants of Galega orientalis cv. NBS-75 (1.05 mg%) at the flowering stage and minimal – in the leaves of the plants of Galega orientalis cv. Kavkazskiy branets (0.31 mg%) at the spring vegetation period. The results showed the ratio of chlorophylls content (a/b) was in range from 3.12 (Galega orientalis cv. Kavkazskiy branets at the fruitage) to 10.10 (Galega orientalis cv. Saliut at the spring vegetation). Maximal and minimal ratio between chlorophylls and carotenoids content identified for Galega orientalis cv. NBS-75 and was in range from 2.40 (budding stage) to 6.79 (spring vegetation stage).